Front Cover: Platelet Releasate Proteome Profiling Reveals a Core Set of Proteins with Low Variance between Healthy Adults. Issue 15 (8th August 2018) - Parsons, Martin E. M.; Szklanna, Paulina B.; Guerrero, Jose A.; Wynne, Kieran; Dervin, Feidhlim; O'Connell, Karen; Allen, Seamus; Egan, Karl; Bennett, Cavan; McGuigan, Christopher; Gheveart, Cedric; Ní Áinle, Fionnuala; et al.
Abstract : DOI:10.1002/pmic.201800219 Upon activation, platelets release a powerful cocktail of soluble and vesicular signals, collectively termed the 'platelet releasate'. In article number 1800219, Parsons et al. use label‐free quantitative (LFQ)‐proteomics analysis to provide a reproducible, quantifiable investigation of the platelet releasate from 32 healthy adults. Their results show that the platelet releasate has low‐population variance among healthy adults, rendering it a potentially useful platform for diagnostic fingerprinting of platelet‐related disease.